Protecting Nurses from Mistreatment by Patients: A Cross-Sectional Study on the Roles of Emotional Contagion Susceptibility and Emotional Regulation Ability - Bing Liu (International Journal of Environmental Research and Public Health, 2021)
In recent years, patient mistreatment of healthcare workers, especially nurses, has been frequent, endangering the interests of organizations while also threatening nurses’ own development. This study aims to examine from the perspective of nurses’ personal interests whether mistreatment by patients decreases nurses’ workplace well-being and career commitment, and how their susceptibility to emotional contagion and emotional regulation ability might mitigate these negative effects. This study adopted a cross-sectional study design (data were collected through self-reported questionnaires with a two-month time lag between the months of August–October 2017). A total of 289 nurses from three hospitals in Shandong province, China, were recruited to participate in our study. The results reveal that mistreatment by patients is negatively related to nurses’ workplace well-being and career commitment. Emotional contagion susceptibility moderates the relationships between mistreatment by patients and career commitment, while there is no significant buffering effect of mistreatment by patients on workplace well-being. Emotional regulation ability moderates the relationships between mistreatment by patients and both workplace well-being and career commitment. These results suggest that improvements in nurses’ emotional regulation ability and susceptibility to emotional contagion can alleviate the harmful impacts of mistreatment by patients.